The antecedent of citizen intention use of e-government service - Taqwa Hariguna; Chung-Wen Hung; Husni Teja Sukmana (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
The purpose of this study was to integrate citizen perceived value into an expectation- confirmation model (ECM) and to explain citizen intention use of e-government services. After reviewing both ECM and citizen perceived values, integrated models were designed. This study was compared to the basic ECM; this study revealed that the integration of ECM with citizen perceived value can provide a concerted solution to illustrate some factors and how it can influence citizen intention use for e-government services.